The barriers in the implementation of mathematics learning for slow learner during the COVID-19 - Hidayatul Wafiroh; Harun Harun (Jurnal Elemen, 2022)
Slow learners also carry out the implementation of online learning at inclusive elementary schools. Online learning conditions are different from face-to-face learning, and it becomes a challenge for teachers to deliver mathematics learning for slow learner students. Learning mathematics is a learning that is considered difficult by slow learner students. It is because slow learner students have limited cognitive abilities and understanding of symbols, abstracts, and concepts. This study aimed to determine the obstacles in the implementation of mathematics learning, which includes the planning, implementation, and assessment stages for slow learner students at inclusive elementary schools. This research is qualitative research with a descriptive approach, and the subjects were ten inclusive elementary school class teachers in Sleman. The data were collected by interview and analyzed with the help of Atlas.ti software. Based on the analysis results, teachers experienced barriers in implementing online learning. The teacher experienced barriers in planning learning media and limited learning resources specifically for slow learner students at the planning stage. The most significant barriers come from the students' condition at the implementation stage, and another barrier comes from parents and teachers. Furthermore, the barriers in the assessment stage included the limitations of distance and time, the validity of the answers, student independence, and decreased enthusiasm of students for working.